2016
DOI: 10.4049/jimmunol.1500630
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol-3,4-Bisphosphate and Its Binding Protein Lamellipodin Regulate Chemotaxis of Malignant B Lymphocytes

Abstract: Cell migration is controlled by PI3Ks, which generate lipid messengers phosphatidylinositol-3,4,5-trisphosphate and phosphatidylinositol-3,4-bisphosphate [PI(3,4)P2] and consequently recruit pleckstrin homology (PH) domain–containing signaling proteins. PI3K inhibition impairs migration of normal and transformed B cells, an effect thought to partly underlie the therapeutic efficacy of PI3K inhibitors in treatment of B cell malignancies such as chronic lymphocytic leukemia. Although a number of studies have imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 65 publications
0
13
0
1
Order By: Relevance
“…For example, in B cells, SHIP1 catalyzes an important production of PI(3,4)P 2 . Evidence has been provided that PI(3,4)P 2dependent processes may contribute to the therapeutic efficacy of PI 3-kinase inhibitors in B-cell malignancies (23). The role of SHIP1 is different in T cells, where it can have multiple functions [reviewed in (24)].…”
mentioning
confidence: 99%
“…For example, in B cells, SHIP1 catalyzes an important production of PI(3,4)P 2 . Evidence has been provided that PI(3,4)P 2dependent processes may contribute to the therapeutic efficacy of PI 3-kinase inhibitors in B-cell malignancies (23). The role of SHIP1 is different in T cells, where it can have multiple functions [reviewed in (24)].…”
mentioning
confidence: 99%
“…PI(3,4)P 2 is produced by PI3-kinase (PI3K) from PI(4)P, as is Phosphatidylinositol (3,4,5)-trisphosphate (PIP 3 ), which is also known to be an important signaling PI, as represented by Akt activation ( Manning and Toker, 2017 ). Although PI(3,4)P 2 has received less attention, several emerging pieces of evidence have indicated the unique and critical importance of PI(3,4)P 2 , such as in spatially localized PI3K signaling ( Braccini et al, 2015 ), endocytosis ( Posor et al, 2013 ; Boucrot et al, 2015 ), neuronal death ( Sasaki et al, 2010 ), membrane ruffling ( Hogan et al, 2004 ), and cell migration ( Bae et al, 2010 ; Li et al, 2016 ). PI(3,4)P 2 has been known to bind some membrane-associated proteins ( Hogan et al, 2004 ; Li and Marshall, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence suggests that PI(3,4)P 2 , which is generated from PIP 3 , not only induces the activation of Akt, but can act independently to regulate processes such as of membrane ruffle formation, podosome formation, lamellipodia formation, and lamellipodia maturation . Recent study showed that PI(3,4)P 2 depletion impairs motility during B cell chemotaxis, and that Lpd, whose PH domain specifically binds to PI(3,4)P 2 , co‐localizes with PI(3,4)P 2 to mediate directional migration . Thus, PI(3,4)P 2 is an important signaling molecule that is involved in regulating cytoskeletal rearrangements at the plasma membrane .…”
mentioning
confidence: 99%
“…(35) Recent study showed that PI(3,4)P 2 depletion impairs motility during B cell chemotaxis, and that Lpd, whose PH domain specifically binds to PI(3,4)P 2 , co-localizes with PI(3,4)P 2 to mediate directional migration. (36) Thus, PI(3,4)P 2 is an important signaling molecule that is involved in regulating cytoskeletal rearrangements at the plasma membrane. (37) Other studies have demonstrated the role of Lpd in the actin cytoskeletal network.…”
mentioning
confidence: 99%